Serangan Hama Belalang (Oxya spp.) pada Tanaman Talas (Colocasia esculenta L.) di Kelurahan Situ Gede Kecamatan Bogor Barat Kota Bogor - Fahira Hanifah; Yayi Munara Kusumah (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Taro (Colocasia esculenta L.) is a plant that has many benefits for human life. Starting from the leaves to the tubers which are widely used as medicine and for food. It is undeniable that taro leaves have many benefits, but it is unfortunate that many farmers still lack the use of taro leaves due to pest damages. This study aims to determine the infestation of locust pests (Oxya spp.) on taro plants (Colocasia esculenta L.) in Situ Gede Village, West Bogor District, Bogor City, which is located in the land owned by Mr. Amran, one of the farmers there. The time of the research is 2 weeks, starting from 20 February 2020 until 3 March 2020. This research was conducted by survey method or by direct observation at the research location. The results of the study of the percentage of locust pest (Oxya spp.) on taro plants (Colocasia esculenta L.) in Situ Gede Sub-District, West Bogor District, Bogor City is 35.5%. Keywords: Oxya spp., Percentage, Symptoms, Taro